Rapid and Economical Colorimetric Detection of Cyanide in Blood Using Vitamin B12. Issue 1 (2nd January 2016) - Chaudhary, Muhammad Taimoor; Sarwar, Muhammad; Tahir, Ammar M.; Tahir, Muhammad Ashraf; Mustafa, Ghulam; Wattoo, Sardar Ali; Imran, Muhammad; Subhani, Adeel
Abstract : This work was aimed at the development and validation of an economical colorimetric method for detection of cyanide in whole blood. The method was based on the reaction of hydrogen cyanide with vitamin B12. The hydrogen cyanide is released on acidification of the blood sample. The vitamin B12 was loaded on a strip of a commonly used filter paper by impregnating the strip in a 1.0% (w/v) solution of vitamin B12 under alkaline conditions. The limit of detection of this method was found to be 1.0 mg L −1 which is lower than the reported lethal blood concentration of cyanide (2.5 mg L −1 ). The method was free from interferences from the common gases including ammonia, carbon dioxide, arsine, phosphine and carbon monoxide, thiocyanate, organophosphate pesticides and nitrile-containing pesticides. This method was successfully employed for detection of cyanide in several cases reported to the forensic toxicology.